β-sitosterol alleviates dextran sulfate sodium-induced experimental colitis via inhibition of NLRP3/Caspase-1/GSDMD-mediated pyroptosis - Zhang, Di; Ge, Fei; Ji, Jing; Li, Yu-Jing; Zhang, Fu-Rong; Wang, Shu-Yan; Zhang, Shu-Jing; Zhang, Dong-Mei; Chen, Meng (Frontiers in Pharmacology, 2023)
Current therapeutic drugs for ulcerative colitis (UC) are not entirely promising with many effects or disadvantages. Though the precise etiology of UC remains unknown, the inflammatory response is definitely involved. Pyroptosis is a newly found form of proinflammatory programmed cell death and plays a critical role in UC, thus bringing new sights into therapy. Now, alternative therapeutic medication from natural products is of interest in research. β-sitosterol (SIT) is a bioactive phytosterol and naturally plentiful present in organisms, which is easily available and harmless. Research on SIT has suggested its potential therapeutic or beneficial roles in UC while the role of pyroptosis is rarely studied. Here, we established UC model on rats and Caco-2 inflammation model in vitro treated with UC. After intervention with SIT, we found that SIT could attenuate colonic injury in rats and protect Caco-2 from DSS-induced cell damage. SIT not only downregulated the production of proinflammatory factors but also suppressed the NLRP3/Caspase-1/GSDMD-mediated signaling. We also observed that SIT restores the colonic barrier integrity. In a word, our work highlighted that SIT might be a promising therapy for UC by taking the anti-inflammation and antipyroptosis effects; and our findings fill some gaps between the therapy for UC and SIT application.